ANALISIS PENDAPATAN USAHA PENANGKAPAN IKAN LAUT MENGGUNAKAN ALAT TANGKAP GILL NET DI DESA TABANIO KECAMATAN TAKISUNG KABUPATEN TANAH LAUT - Yarna Hasiani; Emmy Sri Mahreda; Irma Febrianty (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2019)
This study aims to determine the business benefits gill net fishing net of proceeds for fishing laborers and analyze their feasibility in the sea fishing using gillnet gear. The research activities conducted in the Village Tabanio, Takisung District, of Tanah Laut, a fishing village in the district of Tanah Laut where people predominantly use gill net gear. The data collected is cross section data are sourced directly from the fishing vessel owner/gill net gear, through a structured interview technique (using questionnaires). The results showed that the benefits of fishing vessel owners fishing effort bygill nets in the village Tabanio is an average of Rp.7.634.223 per trip or per month.Fishing effort by gill nets in the village Tabanio profitable and worth the effort, because the value of Rp.61.550.000 positive NPV, the net value of BCR is more thanone (1.38) and IRR over a discounted rate (27% > 14%), and the payback period isfaster than the projected five-year period (2.96 years).